The effect of weather on critic ratings and auction prices for Stellenbosch Bordeaux blends from 2001-2021. - Everts, Charl Jan (School of Economics, 2025)
Growing season conditions are crucial in determining the quality of grapes in a vineyard. Identifying the climate variables with the greatest effect is therefore of interest to viticulturists and winemakers. Continued warming is evident for Stellenbosch since 2001, especially the last ten years. This study models the effect of temperature and rainfall variables on wine quality, represented by wine ratings and auction prices for Stellenbosch Bordeaux-style red wines. Findings indicate that, in terms of the relationship between weather and wine quality, Stellenbosch aligns more closely with Australia than Bordeaux. Growing season temperatures and harvest rainfall play a significant role in determining the outcome of a vintage. An optimal growing season temperature is estimated at 20.5°C. A climate-based vintage heuristic suggests that vintages with growing season temperatures near 20.5°C and January-February rainfall below 60mm are more likely to be exceptional. The heuristic suggests that the 2008 and 2011 vintages are undervalued, and a great 2024 vintage is to be expected. Rating inflation is evident for the portfolio of wines assessed. Similarly, inflation-adjusted auction prices for these wines have increased more than 5% annually. This price growth represents real value appreciation, suggesting that rating inflation may be attributed to objectively better wines. Proven adaptation strategies will be critical as warming and rainfall variability intensify. The increase in ratings and auction prices may already reflect successful farmer adaptation. While Stellenbosch winemakers have demonstrated resilience, increasing water scarcity may elevate the importance of winter rainfall effects, mirroring trends seen in Bordeaux.